Skp1p and the F-Box Protein Rcy1p Form a Non-SCF Complex Involved in Recycling of the SNARE Snc1p in Yeast - Galan, Jean-Marc (American Society for Microbiology, 2001)
Skp1p–cullin–F-box protein (SCF) complexes are ubiquitin-ligases composed of a core complex including Skp1p, Cdc53p, Hrt1p, the E2 enzyme Cdc34p, and one of multiple F-box proteins which are thought to provide substrate specificity to the complex. Here we show that the F-box protein Rcy1p is required for recycling of the v-SNARE Snc1p in Saccharomyces cerevisiae. Rcy1p localized to areas of polarized growth, and this polarized localization required its CAAX box and an intact actin cytoskeleton. Rcy1p interacted with Skp1p in vivo in an F-box-dependent manner, and both deletion of its F box and loss of Skp1p function impaired recycling. In contrast, cells deficient in Cdc53p, Hrt1p, or Cdc34p did not exhibit recycling defects. Unlike the case for F-box proteins that are known to participate in SCF complexes, degradation of Rcy1p required neither its F box nor functional 26S proteasomes or other SCF core subunits. Importantly, Skp1p was the only major partner that copurified with Rcy1p. Our results thus suggest that a complex composed of Rcy1p and Skp1p but not other SCF components may play a direct role in recycling of internalized proteins.